Recollections of my nonexistence - Solnit, Rebecca 1961- (Viking, 2020)
"In this memoir, celebrated author, historian, and activist Rebecca Solnit relates how she found her voice as a writer and as a feminist during the 1980s in San Francisco, in an atmosphere of gender violence on the street and the exclusion of women from cultural arenas. Then in her early twenties, Solnit tells of being poor, hopeful, and adrift in the city, which became her great teacher; of the small apartment she found, which became a home in which to metamorphosize; of how punk rock gave form and voice to her own fury and explosive energy. Solnit explores the way some men attempted to erase her, to shut her up, keep her out and challenge her credibility, as well as contemplating other kinds of nonexistence of groups for gender, ethnicity, and orientation. Her book ends with what liberated her as a person and as a writer--books themselves, the gay men and community who presented a new model of what else gender, family, and celebration could be, and her awakening to the spacious landscapes of the American west, which taught her how to write in the way she has ever since. Recollections of My Nonexistence connects Solnit's hugely popular polemical feminist writings of the last decade with the more lyrical, personal writing of her beloved earlier books A Field Guide to Getting Lost and The Faraway Nearby. This book is for everyone who has endured erasure and dismissal while coming of age in male-dominated spaces"--
Keywords: Solnit, Rebecca -- 1961-; Solnit, Rebecca; Women authors, American / 20th century / Biography; Women / United States / Social conditions / 20th century; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / Women; SOCIAL SCIENCE / Women's Studies; Women / Social conditions; Women authors, American; United States; Women authors / Biography; 1900-1999; Autobiographies; Biographies; Autobiografie